Selection results on subtropic fruit crops in the Russian Federation - M. D. Omarov; Z. M. Omarova (Новые технологии)
The article presents the data of breeding studies on some subtropical fruit crops (Diospyros kaki L., Feijoa sellowiana Berg) cultivated in the Black Sea coast area of the Russian Federation. The first domestic ‘Khostinsky’ persimmon variety has been obtained, which has high productivity and quality of fruits, and is also resistant to pests and diseases. As a result of interspecific crossbreeding, a promising interspecific hybrid No. 99 (Omarov’s ISH) has been obtained (Djiro ’x common persimmon), which is highly frost-resistant can withstand temperature drops to minus 230.  Creation of such hybrids will expand the distribution area of the culture in more northern regions. The amount of sugars in fruits reaches 25% compared with 14-19 % in the control. As a result of multi-year research on feijoa plants cultivated in the humid subtropics of the Russian Federation, many promising forms have been identified among seed populations, three of them («Dagomysskaya», «Dachnaya», «Sentyabrskaya») were cultivated and included in the State Register of protected breeding achievements (plant varieties) of the RF in 2016. Selection of high-yield and especially early ripe forms of feijoa with their further vegetative propagation will increase significantly the area under the culture in the Russian Federation, and will increase the yield of plantations and improve the quality of fruits.